Emotional Intelligence as Mediator between Leadership Styles and Leadership Effectiveness: A Theoretical Framework - Badri-Harun, Azamudin; Zainol, Md Radzi; Amar, Amzairi; Hussain Shaari, Zullina (International Review of Management and Marketing, 2016)
The study intentionally focused on the relationship between leadership styles and leadership effectiveness where emotional intelligence is drawn on as mediator of the relationship. Until recently, there is little or no research related to the intended study. Hence, an initiative to conduct the study has been made to assess their relationships. The theoretical framework is built on the bases of literature. The study centers on an oil and gas multinational in Malaysia, which has extensively expanded with the increase of the volume of supply and demand in that particular market. Is there any significant relationship between the variables? Or, are there any other factors that are excluded that influence the relationship? These questions might be answered when actual study is to take place deploying the respective theoretical framework. Keywords: Leadership Styles, Emotional Intelligence, Leadership Effectiveness JEL Classifications: J29, L22